(untitled) (Journal of the Management Sciences, 2024)
The study determined the effect of employee grievance on job commitment in Nnamdi Azikiwe University, Awka, Anambra State. The study adopted survey research design and data were generated through the questionnaires administered to the respondents. The population of the study comprised 2637 academic staff of Nnamdi Azikiwe University, Awka. The data generated in response to the questions was analyzed and hypotheses were tested using Simple Regression via SPSS version 20 at 5% level of significance. The result revealed that employee dissatisfaction and perceived unfair practices have effect on job commitment in Nnamdi Azikiwe University, Awka, Anambra State and this effect was statistically significant. The findings indicates that employee dissatisfaction, and perceived unfair practices has effect on job commitment in Nnamdi Azikiwe University, Awka, Anambra State, and this effect was statistically significant. This study concludes that employee grievance on performance of Nnamdi Azikiwe University, Awka, Anambra State. Based on the findings, the study recommends that employees that have job dissatisfaction have relatively negative emotions to their jobs, there is need for job satisfaction, hence, employees who have high job satisfaction have positive emotions to their jobs